Modeling and Analysis of Column Formwork Construction Components Using Dynamo Revit (Study Case : Project Construction of Building 2 Hermina Hospital Pandanaran) - Arifin, Muhammad Faizal Ardhiansyah; Oktaviani, Dianita Putri; Budiwirawan, Agung -; Ilingono, Luke Timor (Aceh International Journal of Science and Technology, 2024)
The construction industry in Indonesia continues to experience rapid growth. However, there are still challenges in implementing Building Information Modeling (BIM) technology, particularly in the volume calculation of formwork activity. BIM for formwork activity is generally utilized to calculate the surface area of formwork. Moreover, cast-in-place concrete formwork has many components with different utilities; thus, it is difficult to manage. Therefore, this study endeavors to expand BIM by employing BIM to automate the calculation of the formwork components. This research aims to utilize Autodesk Revit and Dynamo software to accelerate calculation time and enhance the accuracy of calculating the components of column formwork. The developed model is applied in the Hermina Pandanaran Hospital Building 2 Project as reliability validation of the model. The column formwork construction is modeled using Revit in 3D format, which is subsequently analyzed using the Dynamo script to automatically obtain the complete components of the column formwork activity, including the amount of each component. A comparison of manual calculations between those performed using Dynamo shows a 0% difference percentage, demonstrating the accuracy of Dynamo calculation. Based on the result, the utilization of Revit and Dynamo has proven to increase efficiency in formwork management. The findings of this research can provide insights into construction practitioners to leverage BIM technology in enhancing the efficiency and accuracy of column formwork components' volume calculations.